Clinical Usefulness of Urinary Fatty Acid Binding Proteins in Assessing the Severity and Predicting Treatment Response of Pneumonia in Critically Ill Patients: A Cross-Sectional Study. Issue 19 (May 2016) - Tsao, Tsung-Cheng; Tsai, Han-Chen; Chang, Shi-Chuan
Abstract : Abstract: To investigate the clinical relevance of urinary fatty acid binding proteins (FABPs), including intestinal-FABP, adipocyte-FABP, liver-FABP, and heart-FABP in pneumonia patients required admission to respiratory intensive care unit (RICU). Consecutive pneumonia patients who admitted to RICU from September 2013 to October 2014 were enrolled except for those with pneumonia for more than 24 h before admission to RICU. Pneumonia patients were further divided into with and without septic shock subgroups. Twelve patients without infection were enrolled to serve as control group. Urine samples were collected on days 1 and 7 after admission to RICU for measuring FABPs and inflammatory cytokines. Clinical and laboratory data were collected and compared between pneumonia and control groups, and between the pneumonia patients with and without septic shock. There were no significant differences in urinary levels of various FABPs and inflammatory cytokines measured on day 1 between control and pneumonia groups. Urinary values of intestine-FABP ( P  = 0.020), adipocyte-FABP ( P  = 0.005), heart-FABP ( P  = 0.025), and interleukin-6 ( P  = 0.019) were significantly higher and arterial oxygen tension/fraction of inspired oxygen (PaO2 /FiO2, P/F) ratio ( P  = 0.024) was significantly lower in pneumonia patients with septic shock on day 1 than in those without septic shock. After multivariate analysis, adipocyte-FABP was the independent factor ( P  = 0.026). Urinary levels of FABPs measured on day 7 of pneumonia patients were significantly lower in the improved than in nonimproved groups ( P  = 0.030 for intestine-FABP, P  = 0.003 for adipocyte-FABP, P  = 0.010 for heart-FABP, and P  = 0.008 for liver-FABP, respectively). After multivariate analysis, adipocyte-FABP was the independent factor ( P  = 0.023). For pneumonia patients required admission to RICU, urinary levels of adipocyte-FABP on days 1 and 7 after admission to RICU may be valuable in assessing the pneumonia severity and in predicting treatment response, respectively. Further studies with larger populations are needed to verify these issues.